SISTEM SAPAAN DALAM BAHASA BUGIS DI DESA WAJOK HILIR KECAMATAN SIANTAN KABUPATEN MEMPAWAH - Siska Damayanti; Hotma Simanjuntak; Amriani Amir (Universitas Tanjungpura, 2019)
Abstract This study focused on the scope of the problem in kinship and non-kinship greetings. This study aimd to describe the greetings of kinship based on blood relations, marital relations and non-kinship greetings in Bugis language in Wajok Hilir, Siantan district, Mempawah Regency. The method used in this study was the method The source of data in this study was the text of the informant's conversation. The technique used was the technique of referring to proficient involvement, fishing techniques and documentary studies. The tool used study was a list of questions, record instruments and stationery. The results of the study concluded that there were 32 Bugis language greetings derived from text through informant conversations. The greeting of blood relations was classified as the greeting of the nuclear family and the greeting of the extended family. Greetings of marital relations can be classified as greetings to husbands by wives, wives by husbands, parents of husbands/ wives, relatives of husbands or children, husbands or wives of in-laws, parents-in-law and children of older brothers/ sisters Non-friendship greetings are classified into greetings in the profession, in religion, positions, customs, older people, younger people, peers, unknown people, newborn babies and greetings for people who have died. Keywords: Extended Family,Greetings, Kinship, Nuclear family, Social Relations